Attribution of the Principal Components of the Summertime Ozone Valley in the Upper Troposphere and Lower Stratosphere - Chang, Shujie; Shi, Chunhua; Guo, Dong; Xu, Jianjun (Frontiers in Earth Science, 2021)
The key factors affecting the variation of the ‘ozone valley’, which appears during the boreal summer in the upper troposphere and lower stratosphere (UTLS) over the South Asian High (SAH) and its adjacent areas, have not been determined. This study has performed statistical analysis to improve the understanding of the roles of the sea surface temperature (SST), tropopause height, and the West Pacific Subtropical High (WPSH) on the ozone valley. We examined the principal components of the zonal deviation of the total column ozone (TCO*) in the UTLS. The variations of the TCO* anomalies show three dominant modes, namely the east-west dipole mode in the low latitude region, the east-west tripole mode in the middle latitude region, and the south-north mode. According to the regression analysis and information flow, the three leading principal components of TCO* variations are related to the SST near Indonesia and the western Pacific Ocean in low latitudes, the tropopause height over the Iranian Plateau (IP), and the strength of the SAH over the eastern part of the Tibetan Plateau (TP), which is linked to the synchronousness between the SAH and the WPSH. For the east-west dipole mode in the low latitude region, composite analysis shows the interaction between the atmosphere and ocean causes the strengthening of the southern trough at 850 hPa and the divergence at 200 hPa, resulting in a decrease of the TCO* in the UTLS near the low latitude region around the TP. For the east-west tripole mode in the middle latitude region, the composite analysis shows obvious negative anomalies over the IP, where the TCO* reduces and the extent of the ozone valley over the IP increases with the rise of the tropopause. Comparatively, the south-north mode shows obvious positive anomalies over the TP, where the TCO* increases and the extent of the ozone valley over the TP decreases with a weak SAH. This mode is closely related to the location of the WPSH. In summary, the leading factors affecting the three dominant modes for the variations of the TCO* anomalies are SST, tropopause height, and the WPSH.